Immunohistochemical Detection of Propionibacterium acnes in the Retinal Granulomas in Patients with Ocular Sarcoidosis - Nagata, Kenji (Sci Rep, 2017)
The etiology of sarcoidosis is still obscure; however, Mycobacteria and Propionibacterium acnes are considered the most implicated etiological agent for sarcoidosis. To investigate whether P. acnes is an etiological agent for sarcoid uveitis, we analyzed the frequency of P. acnes detected within the biopsied retinas from patients with ocular sarcoidosis by immunohistochemistry with a P. acnes-specific monoclonal antibody (PAB antibody). Eleven patients (12 eyes) with sarcoid uveitis were enrolled in this study. Eight patients with rhegmatogenous retinal detachment, two patients with non-sarcoid uveitis, and two patients with vitreoretinal lymphoma were enrolled as controls. In the sarcoidosis group, granulomas were mainly observed in the inner retinal layer filled with CD4+ cells and CD68+ cells, indicating the Th1 immune response. P. acnes, identified as round bodies that reacted with the PAB antibody, were present in 10/12 samples (83%) from 9/11 patients (82%) with sarcoidosis. These round bodies were scattered within the retinal granulomas mainly in the inner retinal layer. In the control group, no round bodies were detected. Our results suggested that P. acnes could be associated with sarcoid uveitis. We hypothesize that sarcoid granulomas may be formed by a Th1 immune response to P. acnes hematogenously transmitted to the retina.